A Semiotic-Cognitive Analysis Of Selected Arab Spring Political Cartoons (2011-2013) - Abdullah, Shifaa Mohammed (2017)
This study analyzed the responses of twenty five Arab postgraduates in USM, Penang, Malaysia in relation to the selected Arab Spring political cartoons from semiotic-cognitive perspectives. A total of five Arab Spring cartoon panels from the year 2011 to 2013 are selected from electronic newspapers and websites, as they reflect Arab Spring events progressively to investigate their denotative and connotative meanings, patterns of interpretations and plurality of meaning. This study utilizes Barthes‘ (1977) visual semiotics and Moriarty‘s (1997; 2005) application of Peirce‘s (1933; 1994) cognitive inferences to investigate visuals Semiotically. This study identified five main themes from the responses; negative intention towards Arab Spring, manifestation of Arab peoples‘ struggle with democracy, the powerful of social media, the reluctant international community offers the Syrian political crisis no compromising solution, and Arab Spring freedom achievement.